Assessment of Anxiety and Depression among Patients with Substance Use Disorder Attending at a selected Rehabilitation Center Kathmandu, Nepal - Regmi, Kalpana; Ban, Rita Kumari; Baniya, Ambika (Journal of Karnali Academy of Health Sciences, 2025)
Background: Anxiety and depression are two important contributors to the global burden of disease. Both conditions are frequently found as comorbidity among patients with substance use disorder and play a major role in its prognosis and relapse. If ignored such psychiatric illness by a mental health professional, can create a gap in the overall treatment outcome of substance use disorder. Methods: A descriptive cross-sectional research design was adopted to assess the level of depression and anxiety among patients with substance use disorder attending a selected rehabilitation center, Kathmandu from March 2019 to May 2019. Data collection was done from 115 respondents using the purposive sampling technique. A Semi-structured interview scheduled and Hospital Anxiety and Depression Scale was used. Collected data were analyzed by using both descriptive as well as inferential statistics. Results: The study findings showed that among 71.3% of respondents, 41.7% had boarder line anxiety and 29.6% of them had anxiety. Similarly, among 48.7 % of respondents, 29.6% had borderline depression and 19.1% of them had depression. The study concluded that there was a significant association between the level of anxiety and type of family (p=0.035). There was a significant positive relationship (p=0.001, r=.328) between anxiety and depression scores. Conclusion: Most of the patients with substance use disorder had borderline anxiety and depression. Likewise, level of anxiety was significantly associated with type of family. It was also concluded that there was significant positive relationship between anxiety and depression scores. So early identification and management of such psychiatric co-morbid conditions is noteworthy. This action would help to reduce severity in future.